John Dewey and American Democracy - Westbrook, Robert B. (Robert Brett), 1950- (Ithaca, N.Y. : Cornell University Press, 2015)
Over a career spanning American history from the 1880s to the 1950s, John Dewey sought not only to forge a persuasive argument for his conviction that "democracy is freedom" but also to realize his democratic ideals through political activism. Widely considered modern America's most important philosopher, Dewey made his views known both through his writings and through such controversial episodes as his leadership of educational reform at the turn of the century; his support of American intervention in World War I and his leading role in the Outlawry of War movement after the war; and his participation in both radical and anti-communist politics in the 1930s and 40s. Robert B. Westbrook reconstructs the evolution of Dewey's thought and practice in this masterful intellectual biography, combining readings of his major works with an engaging account of key chapters in his activism. Westbrook pays particular attention to the impact upon Dewey of conversations and debates with contemporaries from William James and Reinhold Niebuhr to Jane Addams and Leon Trotsky. Countering prevailing interpretations of Dewey's contribution to the ideology of American liberalism, he discovers a more unorthodox Dewey--a deviant within the liberal community who was steadily radicalized by his profound faith in participatory democracy. Anyone concerned with the nature of democracy and the future of liberalism in America--including educators, moral and social philosophers, social scientists, political theorists, and intellectual and cultural historians--will find John Dewey and American Democracy indispensable reading.
Frontmatter -- Contents -- Preface -- Abbreviations -- Prologue: The Making of a Philosopher -- Part One. A Social Gospel (1882-1904) -- 1. The Hegelian Bacillus -- 2. Organic Democracy -- 3. Chicago Pragmatism -- 4. No Mean City -- Part Two. Progressive Democracy (1904-1918) -- 5. Reconstructing Philosophy -- 6. Democracy and Education -- 7. The Politics of War -- Part Three. Toward the Great Community (1918-1929) -- 8. The Politics of Peace -- 9. The Phantom Public -- 10. Philosophy and Democracy -- Part Four. Democrat Emeritus(1929-1952) -- 11. Consummatory Experience -- 12. Socialist Democracy -- 13. Their Morals and Ours -- 14. Keeping the Common Faith -- Epilogue: The Wilderness and the Promised Land -- Bibliographical Note -- Index
In English.
Online resource; title from PDF title page (publisher's Web site, viewed Apr. 18, 2017).
eBooks on EBSCOhost
Keywords: Dewey, John, -- 1859-1952 -- Political and social views; Dewey, John, -- 1859-1952 -- Political and social views; Dewey, John, -- 1859-1952; POLITICAL SCIENCE -- Political Ideologies -- Democracy; Political and social views; democracy and the scientific method, American Liberalism, liberalism in America, pragmatism, theory of democracy